Pengaruh Skarifikasi dan Pemberian Giberellin Terhadap Perkecambahan Benih Tanaman Aren (Arenga pinnata (Wurmb.) Merr.) - Annis Tatik Maryani; Irfandri ' (Universitas Riau, 2008)
The objective of this research was to determine the influence of scarification and giberellin to sugar palm seed (Arenga pinnata (Wurmb.) Meer) germination. The experiment was conducted from june to November 2006. This researsh used Completely Randomized Design (RAL) with two factors that are scarification and concentration of giberellin. The parameters of this research were germination age (day), germination percentage (%) and seedling height (cm). The result of this research showed the interaction between scarification treatment and sugar palm seed soaking in 50 ppm giberellin resulted in better sugar palm seedling growth compared to other combination. Scarification treatment can improve germination of sugar palm seed and giberellin soaking with 50 ppm consentration represented the treatment with the highest growth.